Midazolam for procedural sedation in adults and children. Literature review (Perioperaciina Medicina, 2023)
The use of medicated procedural sedation in ambulatory surgery and in intensive care units has become popular due to increased treatment options for the doctor and increased comfort for the patient. The purpose of this literature review is to highlight studies reporting the efficacy and safety of midazolam as a sedative in adults and children for procedural sedation.
Keywords: midazolam; procedural sedation; ICU